Pneumococcal Vaccine in Adults with Bronchopulmonary Pathology: from Prevention to Treatment - A. M. Kostinov; A. A. Tarasova; K. V. Mashilov (Эпидемиология и вакцинопрофилактика)
Relevance. Community-acquired pneumonia and chronic obstructive pulmonary disease (COPD) remain a serious public health problem in all respects today.Aims. To summarize the studies of domestic authors on the study of the effect of pneumococcal polysaccharide vaccine on various parts of the immune system and their relationship with the clinical course of the disease in patients with COPD and community-acquired pneumonia. We also consider it necessary to discuss the possible mechanisms of therapeutic effects after the introduction of a monovaccine against S. pneumoniae, as well as when it is combined with vaccines against Haemophilus influenzae type b infection, and the effectiveness of various vaccination regimens, including complex ones.Conclusions. Convincing arguments are presented proving that the introduction of vaccines against respiratory infections can have not only a reventive value, but also a therapeutic effect, accompanied by a transient restoration of the immune system parameters, as well as a reduction in the contamination or elimination of S. pneumoniae in patients with chronic pathology of the bronchopulmonary system.